Spindle cell carcinoma of the mandible: Clinicopathological and immunohistochemical characteristics - Haytham Al-Bayaty; Ramaa L. Balkaran (Elsevier, 2016)
Spindle cell carcinoma, a rare variant of squamous cell carcinoma, has propensity to occur in the upper aero digestive tract, including the oral mucosa. In this oral pathology communication, we report the occurrence of this neoplasm in the left mandible as a large fleshy growth with destruction of bone in a 73-year-old Afro-Trinidadian female. The distinction of this tumor from other malignant spindle cell mesenchymal tumors is important. Selective sampling of this specimen for possible transitional areas of squamous and spindle cell appearance, immunohistochemical staining for cytokeratin, vimentin, and S-100 protein are helpful in establishing the diagnosis. According to the patient's insistence, debulking of the tumor was performed under general anesthesia. Eight months later the patient succumbed to the disease.